Provision of abortion by mid-level providers: international policy, practice and perspectives - Marge Berer (The World Health Organization, 2009)
Based on articles found on the PubMed and Popline databases on the provision of first-trimester abortion by mid-level providers, this article describes policies on type of abortion provider, comparative studies of different types of abortion provider, provider perspectives, and programmatic experience in Bangladesh, Cambodia, France, Mozambique, South Africa, Sweden, the United States of America and Viet Nam. It shows that it is safe and beneficial for suitably trained mid-level health-care providers, including nurses, midwives and other non-physician clinicians, to provide first-trimester vacuum aspiration and medical abortions. Moreover, it finds that projects in Kenya, Myanmar and Uganda have successfully trained nurse-midwives to provide post-abortion care for incomplete abortion with manual vacuum aspiration, and that studies in Ethiopia and India have recommended that providers such as auxiliary nurse-midwives should be trained in abortion service delivery to ensure that they provide safe abortions for low-income women. The paper recommends the authorization of all qualified mid-level health-care providers to carry out first-trimester abortions, and it also recommends the integration of training in providing first-trimester abortion care into basic education and clinical training for all mid-level providers and medical students interested in obstetrics and gynaecology. Finally, it calls for documentation of the role of mid-level providers in managing second-trimester medical abortions to further inform policy and practice.